MTG16 contributes to colonic epithelial integrity in experimental colitis. Issue 10 (24th July 2012) - Williams, Christopher S; Bradley, Amber M; Chaturvedi, Rupesh; Singh, Kshipra; Piazuelo, Maria B; Chen, Xi; McDonough, Elizabeth M; Schwartz, David A; Brown, Caroline T; Allaman, Margaret M; Coburn, Lori A; Horst, Sara N; et al.
Abstract : Objective: The myeloid translocation genes (MTGs) are transcriptional corepressors with both Mtg8 −/− and Mtgr1 −/− mice showing developmental and/or differentiation defects in the intestine. We sought to determine the role of MTG16 in intestinal integrity. Methods: Baseline and stress induced colonic phenotypes were examined in Mtg16 −/− mice. To unmask phenotypes, we treated Mtg16 −/− mice with dextran sodium sulphate (DSS) or infected them with Citrobacter rodentium and the colons were examined for ulceration and for changes in proliferation, apoptosis and inflammation. Results: Mtg16 −/− mice have altered immune subsets, suggesting priming towards Th1 responses. Mtg16 −/− mice developed increased weight loss, diarrhoea, mortality and histological colitis and there were increased innate (Gr1 +, F4/80 +, CD11c + and MHCII + ; CD11c + ) and Th1 adaptive (CD4) immune cells in Mtg16 −/− colons after DSS treatment. Additionally, there was increased apoptosis and a compensatory increased proliferation in Mtg16 −/− colons. Compared with wild-type mice, Mtg16 −/− mice exhibited increased colonic CD4;IFN-γ cells in vehicle-treated and DSS-treated mice. Adoptive transfer of wild-type marrow into Mtg16 −/− recipients did not rescue the Mtg16 −/− injury phenotype. Isolated colonic epithelial cells from DSS-treated Mtg16 −/− mice exhibited increased KC (Cxcl1) mRNA expression when compared with wild-type mice. Mtg16 −/− mice infected with C rodentium had more severe colitis and greater bacterial colonisation. Last, MTG16 mRNA levels were reduced in human ulcerative colitis versus normal colon tissues. Conclusions: These observations indicate that MTG16 is critical for colonocyte survival and regeneration in response to intestinal injury and provide evidence that this transcriptional corepressor regulates inflammatory recruitment in response to injury.